PERLINDUNGAN HUKUM TERHADAP PEMBELI YANG BERITIKAD BAIK DALAM PERJANJIAN PENGIKATAN JUAL BELI (PPJB) (STUDI PUTUSAN PENINJAUAN KEMBALI NOMOR: 534PK/PDT/2017) - Oktaviah Oktaviah; Tjempaka Tjempaka (Jurnal Hukum Adigama, 2019)
Land has a high value because it is a place where living creatures live and do their activity. Because of the high value humans which are a social creature will defend/maintain their land. The need for land is higher and because of the lack of land, nowadays it is hard to get land. One of the ways to obtain it is by sale and purchase. To guarantee that a sale and purchase between a buyer and a seller is made, it needs a agreement which is called a sale and purchase agreement as an advance agreement even though it a sale and purchase agreement hasn’t been regulated in the regulation. A sale and purchase agreement is an agreement that grows in everyday practice in society that, until now is still used in a sale and purchase transaction, to ensure the rights and obligation between the seller and buyer, which the content of the agreement is agreed between the parties as long as it abides to the requirements conditions that are required for the validity of agreements.